The interplay of health, economy, and politics in MENA region migration patterns: a panel data analysis (2000–2020) - Jalal Arabloo; Pirhossein Kolivand; Peyman Saberian; Peyman Namdar; Soheila Rajaie; Fereshte Karimi; Arash Parvari; Raziye Alishavandi; Ahad Bakhtiari; Samad Azari (BMC Public Health)
Abstract Background The MENA region experiences a high migration rate. Migration has a profound effect on the demography, health status, labor market and cultural diversity of the region. This study was conducted with the aim of investigating the migration crisis in MENA region. Method This study was conducted with the panel data method in 2023. The data of 20 countries of MENA region were collected from 2000 to 2020. Information of 16 variables were grouped into 5 categories: health, demographic, economic, climatic, and political. FGLS model was used to determine the impact of different variables on the migration in Mena region. Excel 2019 and Stata 13 software were used. Results The model utilized fixed effects while addressing cross-sectional dependence, variance heteroscedasticity, and serial correlation, employing the FGLS method for estimation. Within the health variables, the mortality rate had a positive and significant impact on net migration (C = 1132.915, P < 0.001). Conversely, several health-related factors exhibited negative significant effects: Out-Of-Pocket expenses (C = -1797.265, P < 0.001), Current Health Expenditure (C = -9137.099, P < 0.001), and the mortality rate from communicable diseases (C = -96.206, P < 0.001). From an economic standpoint, both GDP per capita (C = 0.001, P = 0.02) and inflation (C = 4638.81, P < 0.001) were identified as having significant positive effects on migration. In terms of demographics, the total population variable also demonstrated a positive significant effect (C = 0.001, P < 0.001). Additionally, political factors such as Disability-Adjusted Life Years (DALYs) related to conflict and terrorism positively influenced migration (C = 31.991, P < 0.001). Two climatic factors also showed positive contributions to net migration: forest area (C = 5278.538, P < 0.001) and agricultural lands (C = 344.233, P = 0.007). In contrast, CO2 emissions among the climatic variables had a negative effect on net migration (C = -0.483, P < 0.001). Conclusion Migration in the MENA region is driven by demographic, economic, political, and environmental factors. The youthful population and economic challenges fuel migration, while disparities in healthcare and economic conditions exacerbate these trends. Comprehensive policies are needed to address these interconnected challenges. By implementing such strategies, the region can reduce migration pressures and build more stable societies.